Salpianthus macrodontus Extracts, a Novel Source of Phenolic Compounds with Antibacterial Activity against Potentially Pathogenic Bacteria Isolated from White Shrimp - Pedro Ulises Bautista-Rosales; Alexeyevich Jassiel Prado-Murguía; Iza Fernanda Pérez-Ramírez; Rosalía Servín-Villegas; Francisco Javier Magallón-Barajas; Rosendo Balois-Morales; Verónica Alhelí Ochoa-Jiménez; Paola Magallón-Servín (Molecules, 2022)
This study aimed to evaluate the antibacterial activity in vitro of Salpianthus macrodontus and Azadirachta indica extracts against potentially pathogenic bacteria for Pacific white shrimp. Furthermore, the extracts with higher inhibitory activity were analyzed to identify compounds responsible for bacterial inhibition and evaluate their effect on motility and biofilm formation. S. macrodontus and A. indica extracts were prepared using methanol, acetone, and hexane by ultrasound. The minimum inhibitory concentration (MIC) of the extracts was determined against Vibrio parahaemolyticus, V. harveyi, Photobacterium damselae and P. leiognathi. The polyphenol profile of those extracts showing the highest bacterial inhibition were determined. Besides, the bacterial swimming and swarming motility and biofilm formation were determined. The highest inhibitory activity against the four pathogens was found with the acetonic extract of S. macrodontus leaf (MIC of 50 mg/mL for Vibrio spp. and 25 mg/mL for Photobacterium spp.) and the methanol extract of S. macrodontus flower (MIC of 50 mg/mL for all pathogens tested). Both extracts affected the swarming and swimming motility and the biofilm formation of the tested bacteria. The main phenolic compounds related to Vibrio bacteria inhibition were naringin, vanillic acid, and rosmarinic acid, whilst hesperidin, kaempferol pentosyl-rutinoside, and rhamnetin were related to Photobacterium bacteria inhibition.